Compensation liability in canon law. A draft for a theoretical justification - Michowicz, Przemysław (Prawo Kanoniczne, 2020)
The conceptual assumptions of the present paper refer to a draft capable of justifying, in terms of theoretical method, the compensation liability for loss or damages in canon law. They do so base on the regime of biding norms and by recalling the content of the apostolic tribunals’ jurisprudence in order to adopt some abstract theories which could validate the remedial liability in the science of canon law. It would not be possible if the conclusions of the analysis could not provide some effective indications related to canon law’s specificity. Among the theories which accuracy can be applicated to the damage or harm as an effect of unlawful activity, the optimal proposition refers to the model of justice as fairness in specific case because it makes its own proposes of the legal Church system.